A Role of Higher Education Institutions in the Development of Life-long Learning Processes - Lech Banachowski (Center for Open and Multimedia Eduacation of the University of Warsaw, 2011)
The following question is considered: "In what way can the higher schools support the processes of life-long learning of their graduates and also of their faculty and students?" A solution is proposed based on building learning community of practice managing joint knowledge repository including Personal Learning Environments (PLE) and e-portfolios. It is shown how to extend ordinary LMS (VLE) system to support processes of life-long learning. The steps made at the Polish-Japanese Institute of Information Technology (PJIIT) are discussed towards implementation of these ideas.